I Am Every Good Thing - Barnes, Derrick D.; James, Gordon C. (New York : Nancy Paulsen Books, 2020)
Illustrations and easy-to-read text pay homage to the strength, character, and worth of a child.
Keywords: Self-confidence in children -- Juvenile fiction; Character -- Juvenile fiction; Self-confidence -- Fiction; Character -- Fiction